Deep ecology or ecosophy: eco-self and ecopsychology for wilderness preservation and sustainability in Edward Abbey’s The Monkey Wrench Gang - Caliskan, Dilek Ünügür (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study presents a compelling and significant perspective on the urgent and transformative power of sustainability and Wilderness preservation, two paramount concerns of the 21st century, as vividly depicted in Edward Abbey's ecosophical fictional work The Monkey Wrench Gang (1975). It delves into the intriguing perspective of madness as a metaphor, symbolising the greed of American society induced by growth myths and calling for an eco-self and ecopsychology. The novel's strong call for an eco-self and ecopsychology underscores the need for personal and psychological change in the face of environmental crises. The book portrays the violent crimes of a gang against the life-threatening machines in defence of the wilderness under the leadership of wild lion-faced Hayduke, a Vietnam veteran diagnosed as a psychopath by the army, making capitalist crimes symbolised by the Mormon politician Bishop Love and the Grand Canyon Dam seeable. Although the Gang's violent actions seem to call for radical environmentalism, the novel reflects deep ecology or ecosophy, calling for an ecological self, Wilderness preservation, and diversity as self-care. This study reads The Monkey Wrench Gang and his autobiographical Desert Solitaire, with a conceptual tool-box made of R. D. Laing's "Mad Society," "economic metaphor," Michel Foucault's self-care, Harvey Cleckley's psychopath, Gilles Deleuze's nomadic thought, Homi Bhabha's hybridity, and Bhabha's the Third Space concepts. For Hybrid Hayduke, the "healthy" psychopath, destroying the Grand Canyon Dam is necessary for fixing the synonymous self and the earth. Ironically, the wild Gang, mirroring societal crime, wants to stop the vicious violence-crime cycle caused by civilisation's wild(er)ness idea.